Begunci in odmevi - Luthar, Breda (Dve domovini, 2017)
In this article I investigate the representation of the "refugee problem" in the Odmevi current affairs program on Slovenian national TV. I aim to explore how conventional, naturalized codes and neutralism as a constitutive element of professional self-presentation in political journalism determined the treatment of the "refugee problem". In this context, I analyze the selection of external or "accessed" voices in the Odmevi studio interview, the discursive framing of interviewees and their placement into the show's narrative. The main findings are a) that the selection and b) the discursive treatment of studio guests in Odmevi's interviews caused or rather enabled the debate on the "refugee problem" to be narrowed to the sphere of legitimate controversy represented by partisan politics. The selection and treatment of accessed voices (interviewees and guests) created the so-called opinion or discursive tunnel, which consequently led to the complete symbolical marginalization of all views that fell outside the parliamentary mainstream and its interests, and hence to treating the problem as a mere sequence of events.
Keywords: Analiza diskurza; Begunci; Discourse analysis; Interviews; Intervjuji; Refugees; Television broadcasting of news; Televizijske informativne oddaje